2024
DOI: 10.1002/anie.202317148
|View full text |Cite
|
Sign up to set email alerts
|

Solvation Structure and Derived Interphase Tuning for High‐Voltage Ni‐Rich Lithium Metal Batteries with High Safety Using Gem‐Difluorinated Ionic Liquid Based Dual‐Salt Electrolytes

Yixing Li,
Fangwei Ding,
Yueyue Shao
et al.

Abstract: Stabilizing electrolytes for high‐voltage lithium metal batteries (LMBs) is crucial yet challenging, as they need to ensure stability against both Li anodes and high‐voltage cathodes (above 4.5V versus Li/Li+), addressing issues like poor cycling and thermal runaway. Herein, a novel gem‐difluorinated skeleton of ionic liquid (IL) is designed and synthesized, and its non‐flammable electrolytes successfully overcome aforementioned challenges. By creatively using dual salts, fluorinated ionic liquid and dimethyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…The diverse behaviors of electrolyte components within the solvation structure at a molecular scale were analyzed to interpret the varying electrochemical properties of electrolytes with and without EC solvent. 42,43 First, the coordination environment of Li + before and after the addition of EC can be characterized by the Fourier transform infrared spectrum (FT-IR). It was observed that the vibration of the EC solvent at 1070 cm −1 indicates its involvement in coordinating with Li + .…”
Section: Resultsmentioning
confidence: 99%
“…The diverse behaviors of electrolyte components within the solvation structure at a molecular scale were analyzed to interpret the varying electrochemical properties of electrolytes with and without EC solvent. 42,43 First, the coordination environment of Li + before and after the addition of EC can be characterized by the Fourier transform infrared spectrum (FT-IR). It was observed that the vibration of the EC solvent at 1070 cm −1 indicates its involvement in coordinating with Li + .…”
Section: Resultsmentioning
confidence: 99%